Bacterial Identification on Freshwater Fish Commodities at Fish Quarantine Center, Quality Control and Security of Fishery Products Surabaya I - Hapsari Kenconojati; Nanik Ning Rahayu; Prayogo Prayogo; Mohammad Faizal Ulkhaq (Journal of Aquaculture Science, 2019)
The potential of freshwater fish cultivation in Indonesia is very large and is increasing every year. The high potential of freshwater and ornamental fisheries commodities and consumption must be developed through domestic and export marketing. The distribution carries the risk of entering and spreading fish pests and diseases, so is it required identification or quarantine is needed to avoid negative impacts from the distribution of fishery commodities. One of the infectious diseases which is known to attack fishery commodities in Indonesia is bacterial disease. Bacteria can cause high mortality in fish and loss for farmers. The purpose of this study is to identification bacteria in freshwater fish commodities. The study was conducted in December 2018 - January 2019 at the Fish Quarantine Center, Quality Control and Safety of Fisheries Products in Surabaya I. Identification of bacteria in this study using conventional methods. The parameters observed were external clinical symptoms that appeared on the body of the fish and internal pathology. The material examined in this study were The samples examined during Field Work Practices were Goldfish, Catfish fry, Common carp, and Koi fish with a total of 64 samples. This research was observative, then the data obtained were analyzed descriptively. The Result bacteria identified in freshwater fish commodities from 64 samples were dominated by Aeromonas hydrophila, Pseudomonas anguilliseptica, Streptococcus sp., Plesiomonas shigelloides, and Micrococcus sp. Keywords : Freshwater fisheries commodities, Bacteria, The Conventional Method